Letter to the Ventura County Community College Board of Trustees from Jane Tolmach - Jane Tolmach:::::: (1973)
A letter from Jane Tolmach to the Ventura County Community College Board of Trustees discussing the planned development of Oxnard College and recommendation to speed up said development.